Detection of SARS-CoV-2 and a possible variant in shelter cats. - Ogi Okwumabua; Nancy Bradley-Siemens; Catherine Cruz; Lauren Chittick; Melissa Thompson (PLoS ONE)
SARS-CoV-2 is the cause of mild to severe acute respiratory disease that led to significant loss of human lives worldwide between 2019 and 2022. The virus has been detected in various animals including cats and dogs making it a major public health concern and a One Health issue. In this study, conjunctival and pharyngeal swabs (n = 350) and serum samples (n = 350) were collected between July and December 2020 from cats that were housed in an animal shelter and tested for the infection of SARS-CoV-2 using real time reverse-transcription polymerase chain reaction (rRT-PCR) that targeted the N1 and N2 genes, and a SARS-CoV-2 surrogate virus neutralization Test (sVNT), respectively. 203 (58%) swab samples were negative (N1 and N2 not detected), 2 (0.6%) were positive (N1 and N2 detected) and 145 (41%) were inconclusive (only N1 detected). Analysis of the N2 region and multiple sequence alignment revealed base-pair deletions and substitutions in the N2 probe binding region of the feline samples RNA extracts in comparison with the positive control and human SARS-CoV-2 sequences in the GenBank database. Substituting the N2 probe with a probe derived from the cat sample amplicon sequences, 123 of 127 (96.9%) of the N2 negative samples returned positive. All but one of the 350 serum samples were negative for SARS-CoV-2 antibody. These observations indicated that although detection of SARS-CoV-2 infection was low in the samples tested, pet cats can harbor the virus and serve as potential source for virus spread that may lead to human infections. Additionally, cats may harbor a yet-to-be described virus that is somewhat related to SARS-CoV-2.